Control of particle generation using ion concentration polarization (ICP) based microfluid platform - Toh, Kin Hun (Nanyang Technological University, 2020)
Microfluidics has been an important method for micro total analysis systems (TAS) making a major impact in many different fields. These devices have many unique advantages that allow us to have precision control on the flow process for in-situ observation. Ion exchange membranes (IEM) can be used to act as a filter allowing only specific ions to flow through creating an important particle transport phenomenon called Ion Concentration Polarization (ICP). This process occurs near the membrane and create an ion enrichment zone and an ion depletion zone. When high voltage is introduced to the microchannel, strong convective mixing was observed due to the formation of a vortex. In observation, results have shown that for a vortex to form, a low Reynolds number is required, and the effects are more prominent at lower ion concentration and higher voltage. In this experiment the phenomena of ICP was studied to see if it can be to control the size of particle generated. Controlling the size of the particle generated is an upcoming trend in nanotechnology and can also be applied in several fields. Tiny particles have a distinct benefit which allows its properties, both physical and chemical, to be different from the bulk material and they are based on the size of the particle. In this project, barium chloride and sodium sulfate are used as the two reactants to create the ICP phenomena with a pressure driven flow. The objective is to better understand how the active control of reaction rate and mixing in microfluidic devices, how reaction rate and mixing affects particle generation. Fabricating the device using polydimethylsiloxane (PDMS) and bonding the microchannel to a glass slide. The two reactants are injecting into the channel. Both reactants contain fluorescence to be able to observe the ICP phenomena and the output is collected to observe the particle size distribution. It was observed that ICP has a prominent effect in controlling the size of particle generation. The size of the particle reduced from 54mm at 0v to 35mm at 100v at the flow rate of 20 µl/hr. The experiment was conducted over 4 flow rates of 20,30,40 and 50 µl/hr. The results have shown that mixing effect has a significant effect on particle generation and the applied voltage plays a more pivotal role in the mixing performance as compared to the flow rate variation.